The horse in literature and film : uncovering a transcultural paradigm - LaRubia-Prado, Francisco (Ecocritical theory and practice., 2017)
This book explores the balancing function that horses play when they become central characters in literature and film. Through close readings of texts from the Middle Ages until the present, covering works from Eastern and Western cultures, the book examines the deep symbolic meaning, cultural significance, and projective power of these animals.